2015
DOI: 10.1088/0004-637x/800/1/20
|View full text |Cite
|
Sign up to set email alerts
|

Combined Co and Dust Scaling Relations of Depletion Time and Molecular Gas Fractions With Cosmic Time, Specific Star-Formation Rate, and Stellar Mass

Abstract: We combine molecular gas masses inferred from CO emission in 500 star forming galaxies (SFGs) between z=0 and 3, from the IRAM-COLDGASS, PHIBSS1/2 and other surveys, with gas masses derived from Herschel far-IR dust measurements in 512 galaxy stacks over the same stellar mass/redshift range. We constrain the scaling relations of molecular gas depletion time scale (t depl ) and gas to stellar mass ratio (M molgas /M * ) of SFGs near the star formation 'main-sequence' with redshift, specific star formation rate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

106
725
11
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 582 publications
(843 citation statements)
references
References 179 publications
(362 reference statements)
106
725
11
1
Order By: Relevance
“…While studies of nearby star-forming galaxies suggest that the surface density of ongoing star formation is most closely tied to the dense H2 gas (Bigiel et al , 2011Leroy et al 2008), observed molecular depletion timescales are much shorter than the inferred quenching timescales. For relatively massive galaxies (M 10 10 M ), spanning a broad range of redshift, current observations point towards molecular depletion timescales of roughly 1 − 2 Gyr (Bigiel et al 2011;Leroy et al 2013;Saintonge et al 2011;Tacconi et al 2010Tacconi et al , 2013Genzel et al 2010Genzel et al , 2015. Moreover, recent work targeting larger samples of lower-mass galaxies conclude that the molecular depletion timescale decreases with decreasing stellar mass, such that infalling satellites at 10 9 M should, on average, exhaust their molecular reservoirs in less than 1 Gyr (Saintonge et al 2011;Boselli et al 2014).…”
Section: Discussionmentioning
confidence: 95%
“…While studies of nearby star-forming galaxies suggest that the surface density of ongoing star formation is most closely tied to the dense H2 gas (Bigiel et al , 2011Leroy et al 2008), observed molecular depletion timescales are much shorter than the inferred quenching timescales. For relatively massive galaxies (M 10 10 M ), spanning a broad range of redshift, current observations point towards molecular depletion timescales of roughly 1 − 2 Gyr (Bigiel et al 2011;Leroy et al 2013;Saintonge et al 2011;Tacconi et al 2010Tacconi et al , 2013Genzel et al 2010Genzel et al , 2015. Moreover, recent work targeting larger samples of lower-mass galaxies conclude that the molecular depletion timescale decreases with decreasing stellar mass, such that infalling satellites at 10 9 M should, on average, exhaust their molecular reservoirs in less than 1 Gyr (Saintonge et al 2011;Boselli et al 2014).…”
Section: Discussionmentioning
confidence: 95%
“…with redshift (see also Riechers et al 2010;Casey et al 2011;Geach et al 2011;Aravena et al 2012Aravena et al , 2016Magnelli et al 2012;Bothwell et al 2013;Saintonge et al 2013;Tacconi et al 2013;Chapman et al 2015a;Genzel et al 2015). …”
Section: H2mentioning
confidence: 95%
“…Thus the stellar mass of the progenitor is M * = 10 10.25 M . Using table 4 in Genzel et al (2015), and assuming that the total gas mass is 1.4 times the molecular gas mass, we obtain Mgas ≈ 10 10.43 M . This value is consistent with gas mass observations in ULIRGs with similar properties (e.g., Solomon et al 1997).…”
Section: Quenching Timescalesmentioning
confidence: 99%
“…Genzel et al (2015) combine multiple observations of CO emission and Herschel far-IR dust measurements of over 500 star forming galaxies, and derive molecular gas masses using different methods. Their sample spans the redshift range 0-3, stellar masses of M * = 10 10−11.5 M , and the relative specific star formation rate (sSFR; see definition there) of log(sSFR/sSFR(ms, z, M * )) = −1.5 − 2.…”
Section: Quenching Timescalesmentioning
confidence: 99%